2021
DOI: 10.6007/ijarbss/v11-i12/11269
|View full text |Cite
|
Sign up to set email alerts
|

The New Experiential Impacts Linked to the Application of Knowledge Management in Businesses

Abstract: In recent times, the emergence of knowledge and its application is fundamental to success and failure, for individuals, societies, business and corporate governance. Therefore, there is the neeed to tap up knowledge, disseminate and use for gaining a competitive advantage, despite the existing difficulties. Hence, having a pre-requisite knowledge on staff recruitment quality, employee's behavior to change management, inadvertent tacit knowledge, and knowledge update programs and their application will help det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Several studies examining the connection between entrepreneurial Orientation and organizational success have produced substantial results in association with business growth and performance (Clement, Huaicheo et al, 2021;Adam, Fuzi et al, 2022;Mintah, Gabir et al, 2022). Most discoveries from such studies have found a substantial and favourable entrepreneurial orientation-innovation nexus.…”
Section: Literature Review and Related Theoretical Basismentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies examining the connection between entrepreneurial Orientation and organizational success have produced substantial results in association with business growth and performance (Clement, Huaicheo et al, 2021;Adam, Fuzi et al, 2022;Mintah, Gabir et al, 2022). Most discoveries from such studies have found a substantial and favourable entrepreneurial orientation-innovation nexus.…”
Section: Literature Review and Related Theoretical Basismentioning
confidence: 99%
“…Geographically, Nigeria was included in the study. In terms of entrepreneurial orientation, knowledge management process and capabilities, organizational resources, staff recruitment quality, employee behaviour to change management, inadvertent tacit knowledge, and knowledge update programs are all influential factors for company performance (Clement, Huaicheo et al, 2021), this is an area where most businesses faced various challenges (Wilson, Perepelkin et al, 2020). Problems in business operations, growth, and management include lack of education and training, fear of discouragement in the event of losses, cost and time limits, and insufficient education (Al-Dhaafri & Alosani, 2020).…”
Section: Research Frameworkmentioning
confidence: 99%
“…More crucially, having acknowledged and echoed the key purpose of SMEs, and the government effort in promoting SMEs growth [ 2 , 7 , 50 , 51 ]. We complement government effort by researching and designing business records management concept to safeguard and sustain SMEs in Ghana and across the globe, emphasizing their complete implementation and use as a check for business growth, decision-making, and survival.…”
Section: Review Of Literaturementioning
confidence: 99%
“…This is an area where SMEs owners faced various challenges in their recordkeeping process including lack of accounting knowledge and absence of specific guidelines for bookkeeping and accounting recordkeeping, fear of discouragement in case of a loss, inadequate education and training skills, and cost and time constraints [ 50 ]. This has contributed to the swift failure of most businesses in the area.…”
Section: Review Of Literaturementioning
confidence: 99%
“…This research is in line with (Amoah & Amoah, 2018;Aremu & Adeyemi, 2011;Aroge, 2012b;Caner, 2010;Edmiston, 2007;Etim, 2010b;Roper, 1997;Taiwo et al, 2012) which indicates that SSEs are engine of economic progress. However, financial, personnel, systems and business resources and the entrepreneurs or investors operational abilities in doing important jobs, records keeping and knowledge management, injecting resources and technology, managerial ability and willingness to delegate, and strategic ability for looking to the future may influence business growth and survival (Clement et al, 2021;Juliana et al, 2021;Roper, 1997). This will help the SMEs sector to be more viability with it ripple effect on economic growth.…”
Section: Regression Analysismentioning
confidence: 99%